STATE AND DEVELOPMENT TRENDS OF FINANCIAL INCLUSION IN UKRAINE (World of finance, 2024)
Introduction. Financial inclusion in Ukraine is an important component of the country’s economic and social development. It provides availability and access to financial services and products for the entire population, regardless of their social status, financial condition and geographical location. Here are some key aspects of financial inclusion in Ukraine: banking sector, mobile money and electronic payments, development of macro-financial institutions, growth of financial literacy, regulation and protection of consumer rights, reduction of financial vulnerability, increasing role of international cooperation. Financial inclusion in Ukraine is an important factor for increasing the country’s economic well-being and stability. However, there are challenges, such as ensuring access to financial services in rural regions and increasing the level of financial literacy of the population, which require attention and solutions for the further development of this direction.The purpose of the article is to determine the features of the current state of financial inclusion in Ukraine, as well as to present the main trends of its development.Results. The article analyzes the difference between the concepts of “inclusion” and “inclusiveness”, presents their main features and differences, which further makes it possible to dis tinguish between these categories when studying the current state of economic processes. The main trends in the development of financial inclusion in Ukraine are determined based on the trends in the development of financial and economic inclusion in the world. The main features of the current state of economic inclusion in Ukraine are presented.Conclusions. According to the results of the study, it is proven that today, the state of financial inclusion in Ukraine shows a certain progress and expansion of access to financial services. However, there are still certain challenges and tasks that require attention and solutions for the further development of this direction. The main conclusions regarding the state and trends of the development of financial inclusion in Ukraine include the following: growing access to banking services, growth of electronic payments and mobile money, development of macro-financial institutions, focus on improving financial literacy, strengthening cooperation with international organizations. The presented research results make it possible to determine that financial inclusion is an important factor for increasing the economic well-being and stability of Ukraine. The presented trends show some progress in this direction, but it is necessary to continue work to ensure access of all citizens to financial services and further improve financial inclusion in the country.